2005
DOI: 10.1128/jvi.79.21.13362-13372.2005
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Type 1 Glycoprotein E Is Required for Axonal Localization of Capsid, Tegument, and Membrane Glycoproteins

Abstract: Herpes simplex virus type 1 (HSV-1) glycoprotein E (gE) promotes cell-to-cell spread at basolateral surfaces of epithelial cells, but its activity in neurons is less clear. We used the mouse retina infection model and neuronal cell cultures to define the spread phenotype of gE mutant viruses. Wild-type (WT) and gE-null (NS-gEnull) viruses both infected retina ganglion cell neurons; however, NS-gEnull viral antigens failed to reach the optic nerve, which indicates a defect in axonal localization. We evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
90
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(96 citation statements)
references
References 54 publications
(57 reference statements)
6
90
0
Order By: Relevance
“…This interaction may be important for anterograde axonal transport of viral glycoprotein-containing vesicles. A series of studies using deletion mutants of HSV-1 and PrV that do not express pUS9 or gE have also supported a role for these VPs in anterograde axonal transport [96,101,[123][124][125]. To date, a direct link between either pUS9 or gE and kinesin has not been established.…”
Section: Kinesin-viral Protein Interactionsmentioning
confidence: 99%
“…This interaction may be important for anterograde axonal transport of viral glycoprotein-containing vesicles. A series of studies using deletion mutants of HSV-1 and PrV that do not express pUS9 or gE have also supported a role for these VPs in anterograde axonal transport [96,101,[123][124][125]. To date, a direct link between either pUS9 or gE and kinesin has not been established.…”
Section: Kinesin-viral Protein Interactionsmentioning
confidence: 99%
“…Viruses lacking either gE or gI form characteristically small plaques in cell culture and small inoculation site lesions in mice (4,9,18,40,58). In animal models, gE and gI also mediate viral spread in both anterograde and retrograde directions (4,19,44,56).…”
Section: In Animal Models Of Infection Glycoprotein E (Ge) Is Requirmentioning
confidence: 99%
“…Viruses lacking either gE or gI form characteristically small plaques in cell culture and small inoculation site lesions in mice (4,9,18,40,58). In animal models, gE and gI also mediate viral spread in both anterograde and retrograde directions (4,19,44,56).In order to better understand the role of gE in HSV-1 retrograde neuronal spread, we employed a compartmentalized neuron culture system that has been used to study directional neuronal spread of PRV and West Nile virus (12,14,45). In the Campenot chamber system, neurites are contained in a compartment that is separate from their corresponding cell bodies.…”
mentioning
confidence: 99%
“…This property has made alphaherpesviruses invaluable as neural circuit tracers in studies that aim to map the synaptic architecture of the CNS (14). However, the mechanisms that confer such specificity on the spread of infection are not well understood.The study of mechanisms underlying PRV trafficking revealed that the virally encoded membrane proteins Us9, glycoprotein E (gE), and gI are required for the efficient sorting of virions from an infected neuronal cell body into its cognate axon (6,26,29,44,49). Therefore, in the absence of any of these proteins, infection cannot be transmitted efficiently from a presynaptic to a postsynaptic cell (3,23).…”
mentioning
confidence: 99%